Silk coatings on PLGA and alginate microspheres for protein delivery - Wang, Xiaoqin (2007)
Bombyx mori silk fibroin self-assembles on surfaces to form ultrathin nanoscale coatings based on our prior studies using layer-bylayer deposition techniques driven by hydrophobic interactions between silk fibroin protein molecules. In the present study, poly(lacticco- glycolic acid) (PLGA) and alginate microspheres were used as substrates and coated with silk fibroin. The coatings were visualized by confocal laser scanning microscopy using fluorescein-labeled silk fibroin. On PLGA microspheres, the coating was ∼1 μm and discontinuous, reflecting the porous surface of these microspheres determined by SEM. In contrast, on alginate microspheres the coating was ∼10 μm thick and continuous. The silk fibroin penetrated into the alginate gel matrix. The silk coating on the PLGA microspheres delayed PLGA degradation. The silk coating on the alginate microspheres survived ethylenediamine tetraacetic acid (EDTA) treatment used to remove the Ca2+-cross-links in the alginate gels to solubilize the alginate. This suggests that alginate microspheres can be used as templates to form silk microcapsules. Horseradish peroxidase (HRP) and tetramethylrhodamine-conjugated bovine serum albumin (Rh-BSA) as model protein drugs were encapsulated in the PLGA and alginate microspheres with and without the silk fibroin coatings. Drug release was significantly retarded by the silk coatings when compared to uncoated microsphere controls, and was retarded further by methanol-treated silk coating when compared to silk water-based coatings on alginate microspheres. Silk coatings on PLGA and alginate microspheres provide mechanically stable shells as well as a diffusion barrier to the encapsulated protein drugs. This coating technique has potential for biosensor and drug delivery applications due to the aqueous process employed, the ability to control coating thickness and crystalline content, and the biocompatibility of the silk fibroin protein used in the process.